Identifying attitudinal factors related to ideation in creative problem solving - Basadur, Min; Finkbeiner, Carl T.; McMaster University, Faculty of Business (My University, 1983)
Innovation and creative problem solving training are increasingly important topics in organizations facing accelerating change and environmental volatility. This report first surveys how the literature characterizes creative problem solving, suggests how the various approaches to training or explaining creative problem solving may be categorized, and investigates the empi rical research concerning such training. Second, it reports new field research focussing on one particular training approach previously indicated as useful. Four attitudinal constructs related to ideation, the primary cognitive construct of this training approach, are identified. The implications for future theory-building and training policy alternatives are discussed. A speculative model is presented differentiating between "ideation" and "deferral of judgment". A method of categorizing Osborn's brainstorming rules accordingly is suggested.
24, 6 leaves. ; Includes bibliographical reference (leaf 22-23). ;
The authors wish to thank Ian Meadows, Naresh Agarwal, and Harish Jain for their helpful comments on previous drafts of this working paper.
Paper presented at the 91st Annual Convention of the American Psychological Association at Anaheim, California, August 28th, 1983.
Keywords: Problem solving Creative thinking